The Role of Public Information in Borrower Risk Decision Making: A Review of Limitations and Opportunities in Competitive Financing Markets - Tampilang, Adrian Otniel; Rizal, Muhammad (Journal of Economic and Leadership, 2024)
This study aims to explore the influence of public information on borrowers’ decision-making risk in the financing market, considering the constraints and opportunities that exist in a competitive credit environment. Through a literature review, we find that public information, such as financial statements, can reduce information asymmetry between borrowers and creditors, thereby facilitating better decision-making. Although transparent and accurate information can improve market efficiency, we also find that increased decision-making risk occurs when borrowers feel compelled to take higher risks. This highlights the importance of a thorough understanding of the information available. In addition, appropriate regulatory policies are needed to ensure access to relevant information for borrowers without creating incentives to take excessive risks. This study is expected to contribute to the understanding of the relationship between public information and borrower behavior, as well as policy implications for improving the stability of the financing market